CATIROC: an integrated chip for neutrino experiments using photomultiplier tubes. (11th May 2021) - Conforti, S.; Settimo, M.; Santos, C.; Bordereau, C.; Cabrera, A.; Callier, S.; Cerna, C.; De La Taille, C.; Druillole, F.; Dulucq, F.; Lebrin, V.; Lefèvre, F.; et al.
Abstract: An ASIC (Application Specific Integrated Chip) named CATIROC (Charge And Time Integrated Read Out Chip) has been developed for the next-generation neutrino experiments using a large number of photomultiplier tubes (PMTs). Each CATIROC provides the time and the charge measurements for 16 configurable input channels operating in auto-trigger mode. Originally designed for the light emission in water Cherenkov detectors, we show in this paper that its use can be extended to liquid-scintillator based experiments. The ∼ 26000 3-inch PMTs of the JUNO experiment, under construction in China, is a case in point. This paper describes the features of CATIROC with a special attention to the most critical points for its application to the time profile of the light emission in liquid scintillators. The achieved performances in both charge and time measurements can be inputs for future high-precision experiments making use of PMTs or other photo-sensitive detectors.